Evaluation of Dibenzocyclooctyne and Bicyclononyne Click Reaction on Azido‐Functionalized Antifouling Polymer Brushes via Microspotting. Issue 16 (14th April 2022) - Yang, Bingquan; Wang, Yangxin; Vorobii, Mariia; Sauter, Eric; Koenig, Meike; Kumar, Ravi; Rodriguez‐Emmenegger, Cesar; Hirtz, Michael
Abstract: Strain‐promoted alkyne‐azide cycloaddition (SPAAC) has become an indispensable tool in bioorthogonal conjugation and surface immobilization. While numerous studies have focused on enhancing the reactivity of cyclooctynes, a facile method to evaluate the binding efficiency for cyclooctyne‐azide‐based immobilization without any sophisticated facilities is still missing. In the present work, different derivatives of dibenzocyclooctyne/bicyclononyne (DBCO/BCN) linked to either a fluorophore or a biotin‐moiety are patterned on ultra‐low fouling polymer brushes, which can avoid unspecific protein contamination without any prior blocking steps. The polymer brushes are composed of an antifouling bottom block and azide‐terminated top block. The assessment of binding efficiency is conducted on ordered arrays spotted by microchannel cantilever spotting (μ CS) with a normal fluorescent microscope. Both cyclooctynes demonstrate reliable binding performance with azide‐bearing diblock polymer brushes via μ CS, but DBCO shows a higher surface density of molecular immobilization according to the protein binding assays. This work provides a reference for choosing appropriate cyclooctyne to couple with azides and can be useful for the design of biosensors or bio‐platforms for analyte detection, cell capture, and other biological applications. Abstract : Strain‐promoted alkyne‐azide cycloaddition (SPAAC) is an eminent reaction for biorthogonal conjugation and surface immobilization. The binding efficiency for different cyclooctyne‐azide‐based immobilization routes is assessed on azido‐functionalized antifouling polymer brushes via microchannel cantilever spotting. Fluorescence intensity of proteins bound to spotted microarrays is used to enable a quantitative comparison between the different routes.